The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/pec.0b013e31828575d7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of Bullied Children in the Emergency Department

Abstract: Bullying is an important public health issue in the United States. Up to 30% of children report exposure to such victimization. Not only does it hurt bully victim, but it also negatively impacts the bully, other children, parents, school staff, and health care providers. Because bullying often presents with accompanying serious emotional and behavioral symptoms, there has been an increase in psychiatric referrals to emergency departments. Emergency physicians may be the first responders in the health care syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 157 publications
0
9
0
3
Order By: Relevance
“…18 Consistent with research demonstrating that youth with a mental illness are at increased risk of both suicide and bullying victimization, 13,25 significantly more patients presenting with psychiatric complaints than with medical/surgical complaints reported bullying victimization and screened positive for suicide risk. However, when stratified by chief complaint, recent bullying victimization was not significantly associated with suicide risk among psychiatric patients.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…18 Consistent with research demonstrating that youth with a mental illness are at increased risk of both suicide and bullying victimization, 13,25 significantly more patients presenting with psychiatric complaints than with medical/surgical complaints reported bullying victimization and screened positive for suicide risk. However, when stratified by chief complaint, recent bullying victimization was not significantly associated with suicide risk among psychiatric patients.…”
Section: Discussionmentioning
confidence: 56%
“…Multiple logistic regression was used to estimate the adjusted odds (adjOR) and 95% confidence interval (CI) of suicide risk associated with recent bullying victimization after controlling for age, gender, race/ethnicity, insurance type (as a proxy for socioeconomic status), history of diagnosed depression, and self-reported drug use. These demographic and clinical variables were included in the statistical models as covariates because they are robust risk factors for both bullying 18 and suicide 25 in youth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reassuringly, simple questions are available that are valid and effective for exploring bullying in emergency settings. It has been suggested that emergency providers should have a low threshold for screening for bullying in the emergency department, given the high prevalence of perpetration and victimization and correlation with suicide risk; focused screening based on elevated risk determined from clinical assessment seems to be more prudent than broad screening for most emergency settings (see Table 2) [44].…”
Section: Bullyingmentioning
confidence: 99%
“…Así como no siempre es fácil encontrar sintomatología de violencia en un paciente, pudiera ser más difícil diagnosticar el bullying sufrido por un niño. Se informa que en los EE UU de Norteamérica hasta 30% de los niños comunica la exposición a esta victimización que, además de afectar al niño, influye en otros niños, los padres, profesores y proveedores de salud (2) . Por ello la necesidad de alertar y conocer el bullying como un problema de salud pública, en donde el médico tiene un rol en identificar los niños victimizados, de manera de brindarles el apoyo necesario para que desarrollen relaciones saludables (3,4) .…”
unclassified